The Eco-Theology of The Lombok Community in The Tradition of Bau Nyale - Umi Hanik; Nur Khamidah (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
The Bau Nyale tradition is an annual tradition of the Lombok people which has a high sacred value, because it respects the sacrifice of Princess Mandalika. Traditions that are full of sacredness need to be preserved so that there is no bias between the sacred and tourism. Bau Nyale has ecological and theological values ​​for the people of Lombok; this value is interesting to study from a sociological, anthropological and religious perspective. The research is an integrative qualitative research with an ethnomethodological approach, as a way to know the culture of the community directly, the culture of the people here is not only a small community (the community around the Seger beach) but also does not rule out the possibility for a wider reach. The result of this research is that there is a correlation between Man, Nature and God in the Bau Nyale Tradition, this can be seen in the first form, namely the economy (humans), on the basis of awareness of the importance of economic needs that can be fulfilled by the number of visitors to Seger Beach and Mandalika Beach. which makes the Bau Nyale tradition still supported and exists to this day. The second is the environment. The Bau Nyale tradition is not only seen as a tradition of looking for sea worms, but has strong values ​​that are not stated directly, namely preserving the environment on the coast. The divine basis is his view of the Bau Nyale tradition which is based on an understanding of divinity as the basis of habituation that humans cannot rain, arrange constellations, and produce nyale according to their wishes, except for the power of God.